Studi Demografi: Analisis Efektivitas E-Commerce dalam Mendorong Pertumbuhan Industri Ekonomi Kreatif di Era Digital - Rolia Wahasusmia; RA Rodia Fitri Indriani (Public Service and Governance Journal, 2025)
This study examines the impact of e-commerce on the creative economy industry, focusing on crucial issues such as increased visibility, wider market access, and challenges faced by industry players. The main problems identified are fierce competition and limited technological knowledge among creative industry players. The purpose of this research is to explore how e-commerce can be used effectively and sustainably, as well as the importance of support and training for industry players. The research method used is a survey and qualitative data analysis from creative industry players. The results of the study show that e-commerce significantly increases sales and market access, but challenges remain. The conclusion of the study emphasizes the need for collaboration between industry players, the government, and educational institutions to create an ecosystem that supports the sustainable growth of the creative industry.